Usia, Paritas dan Pendidikan Ibu Berhubungan dengan Penggunaan Kontrasepsi IUD di Puskesmas Mergangsan Kota Yogyakarta - Sava Putri Antika Dewi; Nurul Mahmudah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Family Planning Program is a government effort to control population growth and improve family welfare. One of the recommended contraceptive methods is the Intrauterine Device (IUD) due to its high effectiveness and long-term nature. However, IUD use is still influenced by various factors, including age, parity, and maternal education level. This study aims to determine the relationship between age, parity, and maternal education with IUD contraceptive use at the Puskesmas (Community Health Center) Mergangsan in Yogyakarta Municipality. This study employed an analytical design with a case-control approach. The study population was all 470 active Family Planning Program participants in Puskesmas Mergangsan. A sample of 216 respondents consisting of 108 IUD users and 108 non-IUD users were selected using a simple random sampling technique. Data were obtained from secondary data from family planning service records and statistically analyzed using the Chi-Square test for bivariate analysis. The results of the study showed that the majority of IUD users were in a non-risk age group (20–35 years) (69 respondents - 63.9%), had 1–3 children (98 respondents - 90.7%), and had secondary education (52 respondents - 48.1%). The results of the bivariate analysis showed a significant relationship between age (p = 0.000), parity (p = 0.009), and maternal education (p = 0.000) with IUD contraceptive use. The conclusion of this study is that age, parity, and maternal education are significantly related to IUD contraceptive use. Increased education and family planning counseling are needed to encourage more optimal IUD use.